PANCASILA SEBAGAI SUMBER SEGALA SUMBER HUKUM - Anik Kunantiyorini (LPPM Universitas Pekalongan, 2014)
Indonesian people in his life since ancient times have known that didiskripsikan tuham according to each perspective, social interaction with cooperativeness and order and peace alive. The values that live, grow and develop dug by the founders of this country in 1945 as a trial BPUPKI staatsfundamentalnorm or Groundnorm called Pancasila. Pancasila as a system of philosophy, ideology and the basic law of the state in the governance of the state laws of the Republic of Indonesia, is placed on the list as the source of all sources of law, in the sense that all rules undangn Regulations must load and animate the values of Pancasila. In Political Pancasila as the source of all sources of law is a political agrement. Pancasila as the source of all sources of law within the limits of positive law, because the law bersumberkan on religious teachings, rooted in revelation, as Pancasila is not religion.